Pendampingan Baca Tulis Al-Qur’an Di TPQ Masjid Sholikhin RT 04 Butuh Lor Kelurahan Triwidadi - Ummah, Maulida Latifatul; Gutama, Deden Hardan; Rusiyono, Ruwet; Pranita, Arse Yoza; Putri, Estina Dea; Muas, Farid Rahman; Syaroh, Fitria May; Fisdiyah, Imawati; Anifa, Imroatul; Nadliroh, Lubabun; Hak, M. Aji Asnal; Nashrudin, Nashrudin; Muttaqin, Rafie Zaenul; Andini, Rizky; Agustina, Siti Nur; Oktaviana, Vinda (Universitas Alma Ata, 2023)
Determining the object of the problem posed is the background of the problems that arise in the need for maximizing the Al-Quran Education Park (TPQ) as a center for religious character education. The solution proposed by the Thematic Community Service Group II team at Alma Ata University was to integrate learning to read the Koran and the addition of religious knowledge with religious character values for students. The method used by the Thematic KKN team is method PAR (Participatory Active Research). The contribution proposed by the Thematic KKN team is so that TPQ can maximize the role of TPQ in religious character education. For students, can get additional knowledge. for the community, they can support efforts to inculcate religious character education. In conclusion, the existence of TPQ is still essential in society as a place of education for children.Keywords: Caracter Education , Al-Qur'an Education Park (TPQ), Students, Butuh Lor